2020
DOI: 10.1111/ene.14399
|View full text |Cite
|
Sign up to set email alerts
|

Lee Silverman Voice Treatment for dysarthria in patients with Parkinson’s disease: a systematic review and meta‐analysis

Abstract: Approximately 89% of patients with Parkinson’s disease (PD) suffer from dysarthria. Lee Silverman Voice Treatment (LSVT), a behavioral therapy, aims to improve speech and voice functions. The objective was to assess the effectiveness of LSVT compared with other/no speech interventions for dysarthria in patients with PD. Electronic databases, including PubMed, Embase and the Cochrane Library, were searched. The publication date of all included studies was before 6 March 2020. Only randomized controlled trials (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 83 publications
1
24
0
4
Order By: Relevance
“…The reduction of dopamine in PD typically softens the voice and limits the body movements of PwP. Two programs called LSVT-LOUD [43][44][45] and LSVT-BIG [31,[46][47][48] are directly targeted to helping the PwP speak louder and make larger movements, respectively.…”
Section: Rehabilitate Options For Treating Pdmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduction of dopamine in PD typically softens the voice and limits the body movements of PwP. Two programs called LSVT-LOUD [43][44][45] and LSVT-BIG [31,[46][47][48] are directly targeted to helping the PwP speak louder and make larger movements, respectively.…”
Section: Rehabilitate Options For Treating Pdmentioning
confidence: 99%
“…The majority of PwP have speech/voice dysfunction negatively impact communication. LSVT (Lee Silverman Voice Treatment)-LOUD enhances the voice, increases vocal loudness (by improving articulation, vocal quality, and intonation), and positively alters PwP functional skills communication [43][44][45]. PwP also typically have a movement that is slow (bradykinesia) and hesitant (akinesia) with smaller amplitude (hypokinesia).…”
Section: Rehabilitate Options For Treating Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research found that there are a large number of mRNA changes in various brain diseases ( Tao et al, 2019 ; Bucher et al, 2020 ; Guo X. et al, 2020 ; Jiang et al, 2020 ; Wang et al, 2020 ; Yang et al, 2020 ; Yuan et al, 2020 ; Zhu et al, 2020 , 2021 ). Transcriptomic profiles from mRNA sequencing of peripheral blood with urinary tract infection patients showed that all patients with delirium had significant complement system activation compared to non-delirious patients ( Kalantar et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Deep brain stimulation (DBS) is a prospective treatment for PD, especially in patients with dementia, anxiety, and addiction (Tan et al, 2020 ). Novel behavioral treatment techniques may provide new directions for PD patients, such as Lee Silverman Voice Treatment for dysarthria (Yuan et al, 2020 ). From the current research, the inflammatory response is closely related to the occurrence and development of PD.…”
Section: Discussionmentioning
confidence: 99%